Perancangan Pusat Olahraga Pencak Silat di Kabupaten Siak dengan Pendekatan Arsitektur Bioklimatik - Muhammad Ridhwan; Muhd. Arief Alhusaini; R. Lisa Suryani (Jurnal PROYEKSI: Arsitektur dan Perencanaan, 2023)
Pencak Silat martial art is a traditional sport that has been recognized globally as an intangible heritage of Indonesia that must be preserved and cherished. Pencak Silat is also a sport that achieves international levels of excellence, and it is quite popular in Siak Regency. Several athletes from Siak Regency have achieved numerous accomplishments in Pencak Silat, but until now, there is no dedicated Pencak Silat sports center to facilitate their training. To maintain the achievements in Pencak Silat in Siak Regency, a facility that meets the standard requirements of a Pencak Silat sports center is needed. The main facilities include the IPSI Siak Regency facility, the arena, the training facility, the athlete dormitory, and other supporting facilities. The design of the Pencak Silat Sports Center in Siak Regency is considered important and has good potential for development. The concept used in the design is bioclimatic architecture. Bioclimatic architecture is chosen because it can respond to thermal comfort and good lighting aspects, ensuring that users can comfortably engage in activities inside the building. The hope is that the establishment of a dedicated facility for Pencak Silat sports will improve performance and preserve the heritage of Pencak Silat.